1993
DOI: 10.1248/bpb.16.335
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity of Mammalian Hepatic Dermatan Sulfates.

Abstract: Dermatan sulfate-proteoglycans (DS-PGs) were extracted from rabbit, rat and bovine defatted livers by magnesium chloride extraction and DEAE-cellulose chromatography, and then submitted successively to Asahipak GS-520 gel filtration chromatography, Asahipak ES-502N anion exchange chromatography, and cellulose acetate membrane electrophoresis. The disaccharide composition of the glycosaminoglycan chains was determined by differential digestion by chondroitinase ABC, AC, ACII and/or B followed by HPLC for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…We have found previously that highly sulfated CS/DSs in which IdoA-GalNAc(4,6SO 4 ) units amount to nearly 40% of the repeating disaccharides are present in the mouse liver as GAG chains of decorin and/or biglycan, and that IdoA-GalNAc(4,6SO 4 ) units in CS/DS disappeared completely in GalNAc4S-6ST knockout (KO) mice [13] . Presence of CS/DS-E in the mammalian liver had been reported previously [ 14 , 15 ]. Decorin and decorin mRNA were reported to increase in the liver fibrosis [ 16 , 17 , 18 ].…”
Section: Introductionsupporting
confidence: 61%
“…We have found previously that highly sulfated CS/DSs in which IdoA-GalNAc(4,6SO 4 ) units amount to nearly 40% of the repeating disaccharides are present in the mouse liver as GAG chains of decorin and/or biglycan, and that IdoA-GalNAc(4,6SO 4 ) units in CS/DS disappeared completely in GalNAc4S-6ST knockout (KO) mice [13] . Presence of CS/DS-E in the mammalian liver had been reported previously [ 14 , 15 ]. Decorin and decorin mRNA were reported to increase in the liver fibrosis [ 16 , 17 , 18 ].…”
Section: Introductionsupporting
confidence: 61%
“…20,26,27) In this study, DDi-diS B was not detected from all of the samples as shown in Table 1. We therefore estimated that all of the samples tested did not contain DS.…”
Section: Resultsmentioning
confidence: 56%